5R PRINCIPLES FOR SUSTAINABLE HOUSEHOLD WASTE MANAGEMENT - Li Dong, Wang (Asia Pacific Journal of Religions and Cultures, 2025)
The increase in solid waste presents a pressing environmental challenge globally, particularly in expanding economic zones and densely populated regions. A World Bank survey revealed that global waste generation reached 2,010 million tons in 2016 and is projected to rise to 3,400 million tons by 2050. Efficient waste management through the 3R principles (Reduce, Reuse, Recycle) and the 5R framework (Reduce, Reuse, Repair, Recycle, Reject) offers essential strategies for minimizing waste volume and maximizing resource utilization. These principles not only contribute to long-term sustainability but also mitigate the environmental impacts of daily waste production.